Anti-Inflammatory Effects of Low-Level Light Emitting Diode Therapy on Achilles Tendinitis in Rats - Xavier, Murilo; David, Debora Rodrigues; de Souza, Renato Aparecido; Arrieiro, Arthur Nascimento; Miranda, Humberto; Santana, Eduardo Tadeu; Silva, Jose Antonio; Castillo Salgado, Miguel Angel [UNESP]; Aimbire, Flavio; Albertini, Regiane (Wiley-liss, 2010)
Background and Objectives: The present study investigated the effects of low-level light emitting diode (LED) therapy (880 +/- 10 nm) on inflammatory process in a experimental model of Achilles tendinitis induced by collagenase.Study Design/Materials and Methods: Fifty-six male Wistar were separated into seven groups (n = 8), three groups in the experimental period of 7 days and four groups in the experimental period of 14 days, the control group (CONT), tendinitis group (TEND), LED therapy group (LEDT) for both experimental periods, and LED therapy group 7th to 14th day (LEDT delay) for 14 days experimental period. The LED parameters was 22 mW CW of optical output power, distributed in an irradiation area of 0.5 cm(2), with an irradiation time of 170 seconds, the applied energy density was 7.5 J/cm(2) in contact. The therapy was initiated 12 hours after the tendinitis induction, with a 48-hour interval between the irradiations. The histological analysis and inflammatory mediators were quantifiedResults: Our results showed that LED decreases the inflammatory cells influx and mRNA expression to IL-1 beta, IL-6, tumor necrosis factor-alpha (TNF-alpha) in both phase, and cyclooxygenase-2 (COX-2) just in initial phase (P < 0 05).Conclusion: Our results suggest that the anti-inflammatory therapy with low-power LED (880 nm) enhanced the tissue response in all groups We can conclude that the LED was able to reduce signs of inflammation in collagenase-induced tendinitis in rats by reducing the number of inflammatory cells and decrease mRNA expression of cytokines Lasers Surg. Med. 42:553-558, 2010 (C) 2010 Wiley-Liss, Inc.
Keywords: calcaneous tendon; histological analysis; mRNA; RT-PCR; inflammatory mediators